Is it Possible to Predict Massive Bleeding in Nulliparous Women with Placenta Previa? - Orgul, Gokcen; Ayhan, Sule Goncu; Saracoglu, Gulhan Cetinkaya; Yucel, Aykan (Revista Brasileira de Ginecologia e Obstetrícia / RBGO Gynecology and Obstetrics, 2021)
Objective We evaluated risk factors to determine if there were specific risk factors that could predict massive bleeding in nulliparous women with placenta previa.Methods The participants were classified into two groups. Women with a calculated blood loss ≥ 1,000 mL were included in the massive bleeding group. Women without any signs or symptoms related with hypovolemia or with a calculated bleeding volume < 1,000 mL were categorized into the non-massive bleeding group.Results There were 28 patients (40.6%) with massive bleeding and 41 cases (59.4%) with non-massive bleeding. The calculated blood loss and number of cases that required red cell transfusions were statistically different between the groups (< 0.005 and 0.002, respectively). There were no statistically significant differences in terms of maternal or fetal factors, placental location, or delivery characteristics between the two groups.Conclusion We could not determine the predictive features for massive hemorrhage based on clinical features, delivery features, or placental location.
Keywords: cesarean section; nulliparity; placenta previa; postpartum hemorrhage; uterine bleeding